Exploring The Pedagogical Role Of Paralanguage In Behavioral Regulation: The Case Of First Year Middle School - Aya Rahal Marwa, Miss Sabah FarrahAmira Bouzidi (UNIVERSITY OF MOHAMED BOUDIAF, 2022)
Abstract The transition of pupils from elementary school to middle school requires a certain level of learning maturity in order for them to face unfamiliar knowledge in different subjects and to develop learning skills that would help them direct their focus towards their learning and facilitate that process. However, most of pupils display disturbing behaviors in their first year of middle school as a result of their learning immaturity. These disturbing behaviors hinder their learning process and create an unhealthy learning environment. Furthermore, they create a huge obstacle for teachers, especially in their classroom management. Luckily, teachers can regulate these behaviors and help their pupils develop learning maturity using different communication techniques. Regarding pupils' fragility and age, paralanguage seems to be a great assistant for teachers while regulating their pupils' behaviors since it offers a variety of non-verbal cues that can deliver teachers' feelings, attitudes, and opinions about their pupils' behaviors without expressing them verbally, and can be easily captured and understood by kids around that age. However, in such cases, paralanguage shouldn’t be used randomly or spontaneously; a pedagogical and strategic use needs to be followed to make the best use of these tools and to effectively regulate pupils' behavior.s
Keywords: Key terms: Paralanguage, Non-verbal cues, Pedagogical, Behavioral Regulation